Correction: Lithium-containing biomaterials inhibit osteoclastogenesis of macrophages in vitro and osteolysis in vivo. Issue 15 (25th March 2019) - Pan, Chenhao; Chen, Lei; Wu, Ruoyu; Shan, Haojie; Zhou, Zubin; Lin, Yiwei; Yu, Xiaowei; Yan, Liang; Wu, Chengtie
Abstract : Correction for 'Lithium-containing biomaterials inhibit osteoclastogenesis of macrophages in vitro and osteolysis in vivo ' by Chenhao Pan et al., J. Mater. Chem. B, 2018, 6, 8115–8126.